HR, 5th Edition - Angelo DeNisi; Ricky Griffin (Cengage Learning, 2019)
Students save money when purchasing bundled products. This bundle contains HR, 5th Edition, and access to MindTap for 1 term via printed access card. With a single login for MindTap, you can connect with your instructor, organize coursework, and have access to a range of study tools, including e-book and apps all in one place! MindTap helps you learn on your terms. Read or listen to textbooks and study with the aid of instructor notifications, flashcards, and practice quizzes. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.